Analyzing Cooperative Learning Thematically: An Exploratory Case Study With a Composite Qualitative Model (Journal of Education and Development, 2023)
This study explores how educators implement Cooperative Learning (CL) in their teaching methods through an exploratory case study using Saldana's model (2016) as the initial coding framework. Thematic coding, guided by Segev's semantic analysis techniques (2022), uncovered diverse perspectives among participants, highlighting various themes supporting CL models. Nevertheless, a consistent theme that emerged was the central concept of CL within the semantic analysis graph. The amalgamation of semantic analysis and thematic coding combined open and theoretical coding for a comprehensive understanding of the data. Furthermore, the incorporation of semantic discourse evidence strengthened the analysis, resulting in a theoretical representation of CL.